VIHARA DEWI WELAS ASIH: PERKEMBANGAN DAN PERANANNYA DALAM RELASI BUDDHIS-TIONGHOA DENGAN MUSLIM DI CIREBON - Nurman Kholis (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This research applied a qualitative research with historical approach. Data collection techniques were interviews and observation. The purposes of this research were as follows: 1). revealing Dewi Welas Asih Temple development 2). Explaining the role of the Dewi Welas Asih Temple in relation between Buddhist-Tionghoa and Muslims in Cirebon nowadays. The result of this research could be concluded that: 1). Buddhism came and grew in Indonesian archipelago since the 5th century until the 15th century. Over the next five centuries, Buddhist civilization dimmed and then rose again after the formation of Republic of Indonesia in 1945; 2). The historical traces of Buddhism at past was marked by establishment of Dewi Welas Asih Temple in 1595; 3). The relationship between Buddhist-Tionghoa and Muslims was harmonious.